Kroatizmi v jeziku pridigarja Jožefa Horvata - Zver, Nina (Jezik in slovstvo, 2022)
The article deals with the language of sixteen sermons from 1905, written in the Parish of Črenšovci by Jožef Horvat, a Burgenland Croat from Velika Narda who was the chaplain there at the time (1905–1912). These are his first sermons, which he wrote (or attempted to write) in the Prekmurje (literary) language, and they largely show elements of his mother tongue, i.e., Burgenland Croatian, which is based on Chakavian, but also has Shtokavian and Kajkavian features. The language is analysed at the phonetic, morphological and verbal level, focusing on elements that are not common to the Prekmurje and Croatian language areas.
Keywords: Burgenland Croatian language; Burgenland Croats; Chakavian; Croatisms; čakavščina; gradiščanski Hrvati; gradiščanskohrvaški jezik; Horvat, Jožef; jezikovne analize; Kajkavian; kajkavščina; kroatizmi; linguistic analyses; Prekmurje language; prekmurščina; Shtokavian; štokavščina